Ectomycorrhizal and saprotrophic fungi respond differently to long‐term experimentally increased snow depth in the High Arctic. Issue 5 (2nd June 2016) - Mundra, Sunil; Halvorsen, Rune; Kauserud, Håvard; Bahram, Mohammad; Tedersoo, Leho; Elberling, Bo; Cooper, Elisabeth J.; Eidesen, Pernille Bronken
Abstract: Changing climate is expected to alter precipitation patterns in the Arctic, with consequences for subsurface temperature and moisture conditions, community structure, and nutrient mobilization through microbial belowground processes. Here, we address the effect of increased snow depth on the variation in species richness and community structure of ectomycorrhizal (ECM) and saprotrophic fungi. Soil samples were collected weekly from mid‐July to mid‐September in both control and deep snow plots. Richness of ECM fungi was lower, while saprotrophic fungi was higher in increased snow depth plots relative to controls. [Correction added on 23 September 2016 after first online publication: In the preceding sentence, the richness of ECM and saprotrophic fungi were wrongly interchanged and have been fixed in this current version.] ECM fungal richness was related to soil NO3 ‐N, NH4 ‐N, and K; and saprotrophic fungi to NO3 ‐N and pH. Small but significant changes in the composition of saprotrophic fungi could be attributed to snow treatment and sampling time, but not so for the ECM fungi. Delayed snow melt did not influence the temporal variation in fungal communities between the treatments. Results suggest that some fungal species are favored, while others are disfavored resulting in their local extinction due to long‐term changes in snow amount. Shifts in species composition of fungal functional groups are likely to affect nutrient cycling, ecosystem respiration, and stored permafrost carbon. Abstract : Long‐term increase in snow depth imposes negative effect on the richness of ectomycorrhizal fungi, while positive effect on saprotrophic fungi, which suggests that some fungal species are favored, while some fungi may go locally extinct due to changes in the amount of snow.